Mengembangkan Badan Usaha Milik Desa dalam Lingkaran Adat Desa Sanur Kaja - Ni Luh Gede Sujianingsih; Yanti Budiasih (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The establishment of BUMDes basically aims to increase village productivity and ultimately improve the community's economy. The existence of BUMDes in villages, if managed well, can also contribute to a large increase in Village Original Income (PADes), including in Sanur Kaja village. However, the management of village funds for BUMDes in Sanur Kaja village has problems, namely competition between village-owned enterprises and customary-owned enterprises. This research generally aims to create a BUMDes management strategy in Sanur Kaja village so that it does not come into contact with business entities owned by traditional villages. This research use desciptive qualitative approach. Research data was collected using observation, interviews and documentation. From the research, it was found that, technically, the implementation of BUMDes policies in the formation aspect could be implemented well. This can be seen from the process of establishing BUMDes in Sanur Kaja village because administratively it has fulfilled the requirements in the applicable regulations. Factors that support the implementation of BUMDes policies include the size and objectives of the policy, resource support in the form of capital, communication between organizations, social conditions of the community and disposition. The factors that hinder the implementation of BUMDes policies are human resources, the absence of an appropriate strategy, and the character of the implementing agent.